Common Fixed-Point Theorems of Generalized ψ,φ−Weakly Contractive Mappings in b−Metric-Like Spaces and Application - Hongyan Guan; Jianju Li (Journal of Mathematics)
In this paper, we prove some common fixed-point theorems of generalized ψ,φ−weakly contractive mappings in b−metric-like spaces. We also give two examples to support our results. Meanwhile, we present an application to the existence of solutions for a system of integral equations by means of our results.